Do Bats Have the Necessary Prerequisites for Symbolic Communication? - Knörnschild, Mirjam; Fernandez, Ahana A. (Frontiers in Psychology, 2020)
Training animals such as apes, grey parrots or dolphins to communicate via arbitrary symbols with humans has revealed astonishing mental capacities that may have otherwise gone unnoticed. Albeit bats have not yet been trained to communicate via symbols with humans, we are convinced that some species, especially captive Pteropodid bats (‘flying foxes’), show the potential to master this cognitive task. Here, we briefly review what is known about bats’ cognitive skills that constitute relevant prerequisites for symbolic communication with humans. We focus on social learning in general, trainability by humans, associative learning from humans, imitation, vocal production learning and usage learning, and social knowledge. Moreover, we highlight potential training paradigms that could be used to elicit simple ‘symbolic’ bat-human communication, i.e. training bats to select arbitrary symbols on a touchscreen to elicit a desired behaviour of the human caregiver. Touchscreen-proficient bats could participate in cognition research, e.g. to study their numerical competence or categorical perception, to further elucidate how nonhuman animals learn and perceive the world.